2016
DOI: 10.18632/oncotarget.12651
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of melanoma cells selective apoptosis induced by a photoactive NADPH analogue

Abstract: Melanoma is one of the most lethal cancers when it reaches a metastatic stage. Despite the spectacular achievements of targeted therapies (BRAF inhibitors) or immuno-therapies (anti-CTLA4 or anti-PD1), most patients with melanoma will need additional treatments. Here we used a photoactive NADPH analogue called NS1 to induce cell death by inhibition of NADPH oxidases NOX in melanoma cells, including melanoma cells isolated from patients. In contrast, healthy melanocytes growth was unaffected by NS1 treatment.NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 61 publications
1
21
0
2
Order By: Relevance
“…Cells were stained with DAPI and Annexin V or Cell ROX Deep Red and analyzed using fluorescence-activated cell sorter (MACSQuant Analyzer) and MACSQuantify software as described 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Cells were stained with DAPI and Annexin V or Cell ROX Deep Red and analyzed using fluorescence-activated cell sorter (MACSQuant Analyzer) and MACSQuantify software as described 32 .…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, the 3 0 RR is considered as a major lymphoma oncogene deregulator, [3][4][5] and its deletion has no effect on immune and inflammatory responses in the pristane mouse model. It is, thus, tempting to speculate that the 3 0 RR might be considered as a potential suitable target for anti-lymphoma pharmacological therapy without significant impact on the normal immune and inflammatory networks.…”
mentioning
confidence: 90%
“…4 Interestingly the phenotype of lymphoproliferations induced by the c-myc-3 0 RR transgene is affected by the presence of associated mutations in key cell cycle dependent genes such as p53 or Cdk4. 5 Knock-out models have clarified the functions of the 3 0 RR as essential for high-rate IgH transcription at the plasma cell stage. 2 3 0 RR may thus be a potent activator of IgH-translocated oncogene transcription, even when the breakpoints lie several hundred kb away from the 3 0 RR.…”
mentioning
confidence: 99%
“…Indeed, B-cells bearing the same initial oncogenic events can lead to different B-cell lymphoma subtypes if their development is impaired, while different mutations occurring in the same cell of origin can induce similar tumors. 4 In this context, we also show that the 3 0 RR can affect the phenotype of B-cell lymphomas due to oncogene translocation in other loci than the IgH one, by acting on B-cell maturation and regulating potentially oncogenic recombination and mutations during late B-cell differentiation. …”
mentioning
confidence: 54%
“…3 Chromosomal translocations linking oncogenes to these elements are implicated in various B-cell malignancies. [3][4][5] If the deregulation of the translocated oncogene by enhancer elements located in cis was extensively studied, 4,5 little is known about a potential trans effect of the Ig enhancers, for example the role of the IgH 3 0 RR on lymphomagenesis caused by an oncogene translocation to the IgL locus. Indeed, studies have shown that deletion of the 3 0 RR modulates the B-cell fate by lowering the BCR signaling, 6 which is of key importance in B-cell malignancies.…”
mentioning
confidence: 99%